Modern Approaches to Improving the Quality of Education in Higher Educational Institutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the issues of improving the quality of education in higher education institutions. Also, the study of modern trends and models of the quality of education in higher education institutions was analyzed based on modern approaches.